Penanganan resesi gingiva dengan cangkok jaringan ikat palatal: Teknik pouch dan tunnel - Chandra Susanto (Prima Journal of Oral and Dental Sciences, 2020)
Cosmetic procedures have become an essential part of periodontal treatment. One of the commonly used esthetic periodontal procedures is coverage of denuded roots. The recession of gingiva is increasingly becoming a more prominent condition in the oral health of many patients and should be treated at its earliest detection. The correction of class I and II gingival recessions are presented as a means of minimizing surgical trauma and achieving predictable aesthetic results. This report will discuss multiple recession case treated with palatal connective tissue graft using pouch and tunnel technique. 23 years old male was referred to Periodontia Department, Faculty of Dentistry, University of Sumatera Utara for management of multiple gingival recession. Patient diagnosed with class I and II gingival recession caused vigorous toothbrushing. Initial therapy was performed prior to surgical therapy. The technique for denuded root coverage using palatal connective tisue graft with pouch and tunnel technique.  After surgical therapy the gingival recession was totally covered with a beautiful aesthetic result and the healing in donor site progressed uneventfully.   The connective tissue graft procedure led to achievement of satisfying clinical results in the presented case. The application of tunnel technique due to its minimal invasive approach quickens the healing process and allows better aesthetic results.